1998
DOI: 10.1152/ajpcell.1998.275.3.c675
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 action in L6 myotubes is via a receptor different from the pancreatic GLP-1 receptor

Abstract: The incretin hormone glucagon-like peptide-1 (GLP-1)-(7—36) amide is best known for its antidiabetogenic actions mediated via a GLP-1 receptor present on pancreatic endocrine cells. To investigate the molecular mechanisms of GLP-1 action in muscle, we used cultured L6 myotubes. In L6 myotubes, GLP-1 enhanced insulin-stimulated glycogen synthesis by 140% while stimulating CO2 production and lactate formation by 150%. In the presence of IBMX, GLP-1 diminished cAMP levels to 83% of IBMX alone. In L6 myotubes tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 24 publications
12
53
0
1
Order By: Relevance
“…4B), whereas the control animals showed their first sign of peripheral insulin responsiveness (46%) only during the latter infusion step. These data suggest a marked left shift in insulin-stimulated peripheral glucose uptake and are consistent with our previous demonstration of increased glucose uptake in soleus muscle (21) and with several reports of incretin-stimulated increases in glucose uptake (30,39). A number of studies using GLP-1 receptor agonists over the long term have suggested similar improvements in insulin sensitivity (38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4B), whereas the control animals showed their first sign of peripheral insulin responsiveness (46%) only during the latter infusion step. These data suggest a marked left shift in insulin-stimulated peripheral glucose uptake and are consistent with our previous demonstration of increased glucose uptake in soleus muscle (21) and with several reports of incretin-stimulated increases in glucose uptake (30,39). A number of studies using GLP-1 receptor agonists over the long term have suggested similar improvements in insulin sensitivity (38).…”
Section: Discussionsupporting
confidence: 92%
“…Since the early 1990s, numerous studies have revealed a pleiotropy of antidiabetic effects triggered by interaction of the incretins with their respective cell-surface receptors. Among them are stimulation of ␤-cell glucose competence, proliferation, differentiation, growth, and cell survival; inhibition of glucagon secretion; and several reports indicating stimulation of glucose uptake in muscle cells (2)(3)(4)(5)(6)(7)30,31). Recently, we showed that long-term DP IV inhibitor therapy caused marked improvements in glucose tolerance, hyperinsulinemia, and ␤-cell function in the VDF rat, findings that highlight the potential utility of these compounds in diabetes therapy.…”
Section: Discussionmentioning
confidence: 84%
“…The specific activity of the eluted HMGB1 was 2.8 ϫ 10 6 cpm͞g of protein. The cell surface binding of HMGB1 or A box to macrophage cultures was performed according to a described protocol (19). In brief, RAW 264.7 cells were plated in 24-well plates and grown to confluence.…”
Section: Methodsmentioning
confidence: 99%
“…On this basis, Ex9-39 is considered to be an inverse agonist of the GLP-1 receptor (26). In contrast, in some studies Ex9-39 does not antagonize GLP-1 action or may even behave as an agonist (27)(28)(29)(30). These observations raise the possibility that although Ex9-39 effectively antagonized the incretin effect of endogenous GLP-1, the growth-promoting effect was not antagonized.…”
Section: Glp-1 In Pancreatic Regenerationmentioning
confidence: 99%